PENGAWASAN DINAS PENDIDIKAN DAN KEBUDAYAAN TERHADAP IZIN PENYELENGGARAAN PENDIDIKAN ANAK USIA DINI (PAUD) DI KECAMATAN TAMPAN TAHUN 2015 - Darmawan, Febri; ", Ishak (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
In the case of establishment of ECD government make arrangements through the Minister of Education and Culture of the Republic of Indonesia Number 84 Year 2014 On the Establishment of Early Childhood Education Unit. The number of early childhood education in the district handsome in line with a number of problems arise, one of which permit misuse. Early Childhood Education Institutions that have only one license (such as permits TK / TPA / KB) uses his permission to conduct activities other pendiidikan. The problem in this research is how the supervision of the Education and Culture Against an operating license for Early Childhood Education (ECD) In Sub Handsome 2015? The purpose of this study was to determine the supervision Office of Education and Culture Against an operating license for Early Childhood Education (ECD) In Sub Handsome 2015 and obstacles in sight. In this study, researchers used a descriptive research with a qualitative method approach. This research is located at the Technical Implementation Unit of the District Education Office Handsome Pekanbaru. For the research informants using purposive sampling techniques. Data collection techniques used were observation, interviews and documentation. To examine the issues raised in this study, the authors analyze the data using descriptive methodsThe results of this study can be concluded that in the supervision of the Department of Education and Culture Against an operating license for Early Childhood Education (ECD) in the District Charming 2015 has not terlaksa effective, since the scope of the UPTD Handsome very spacious consisting of 60 institutions ECD while labor inspectors only 1 person. Obstacles in the supervision of the Department of Education and Culture Against an operating license for Early Childhood Education (ECD) In Sub Handsome In 2015, the authors describe it as follows: (a) Lack of supervisory personnel, (b) less strict in imposing sanctions, (c) Competition business education that is not healthy.Keywords: Monitoring, Provider License Early Childhood Education